Development Of Pop Up Book To Increase Interest and Learning Outcomes - Komari, Muh.; Widiyaningrum, Priyantini; Partaya, Partaya (Journal of Innovative Science Education, 2022)
The learning of integrated science should be supported by several things including the existence of Learning Media. The reality is that at MTs Putera Sunniyyah Selo, there are not many interesting learning media found. Even though the learning media is very important for the realization of student interest and learning outcomes. Therefore, it is necessary to develop Pop Up Book as a Learning Media. The purpose of this research is to develop Pop Up Book as learning media material on the interaction of living things with the environment, its validity and effectiveness as a learning media, and to find out how much student interest in using of Pop Up Books as a learning media. The method of research is use Research and Development (R&D). The validity test was carried out by media experts and material experts using a questionnaire. The effectiveness of learning media was measured based on the N-Gain value indicator from the pretest-posttest results, as well as the teacher and student response questionnaire scores. Student learning interest is measured based on the questionnaire score of student learning interest. The test of the effectiveness of learning media was carried out at MTs Putera Sunniyyah Selo, Tawangharjo District, Grobogan Regency, in grade VII. The results showed that the validation score of the media expert reached 88.19%, while the validation score of the material expert validation reached 90.69% with an average of 89.44%, which means that the learning media could be elassified valid. The results of the analysis of the effectiveness of the media based on the N-Gain value were 0.8, which means that the increase in the pretest posttest could be classified as high criteria. The scores for the questionnaire responses from teachers and students were 92.50% and 86.46%, both of which were very effective. The percentage of interest in learning reached 90.09% with very good criteria. Based on these indicators, it can be concluded that the Pop Up Book as a Learning Media is declared valid by media and material experts, is effectively used in learning and is able to generate interest in learning at MTs Putera Sunniyyah Selo in the very good category.